Rational redistribution of waste of resources. Manufacturing of equipment for cutting machine - Yu. E. Soloviev; I. A. Kovaleva (Литьë и металлургия)
Almost all metal at OJSC «Byelorussian Steel Works» – management company of holding «Belarusian Metallurgical Company» includes today a mandatory physical-mechanical tests which allow to estimate the parameters of the raw materials, to know the reasons for loss of strength and determine operational characteristics. In the Central Factory Laboratory (CFL), laboratory of physical and mechanical tests (LPMT) for the preparation of samples of reinforcement equipment is used of knives in the cutting machine SIMA GEL-30 for cutting rebar from the mill 320 rolling shop № 1 with a diameter from 6 to 24 mm. In the drop-hummer shop annually discards off for scrap waste up to 50 knives. Hydraulic shears of drop-hummer shop used knives set of production of OJSC «Kobrin tool plant «SITOMO», made of steel grade 30ХСНВФА, according to the TU14-1-4461. The staff of the Central laboratory LFMI proposed to use waste knives drop-hummer shop for the manufacture of knives for the chopping of the machine SIMA GEL-30. On the basis of the conducted researches the technological scheme was developed for production of knives for the chopping of the machine SIMA GEL-30 cold cutting of reinforcing bar mill 320 the rolling shop № 1.